THE CONCEPT OF THE AMORTIZED COST AS THE BASIS FOR THE MODERN SYSTEM OF INTERNATIONAL REPORTING STANDARDS - ANTON Kuzmin (Учёт. Анализ. Аудит, 2019)
The article examines the concept of the amortized cost, which is the basis for the modern system of international reporting standards. This article develops the accounting procedure of an object with a complex irregular structure of payments, which is based on the concept of the amortized cost with the application of the effective interest-rate method. The procedure is applicable in the situation of the discrepancy between the time of payment (for bonds - coupons, for credit - interests, as well as the repayment of the principal of the loan or the face value of the bond)and the time of drawing up of the interim and the closing annual accounts reporting. The procedure is applicable for almost all the cash flows, including non-recurrent, which allows to use its algorithm for accounting purposes in accordance with IFRS for the debt financial instruments, leases and other situations. The proposed algorithm in its general form provides for the revaluation of the financial instruments in the framework of the accounting procedures in accordance with the concept of the amortized cost at any moment of their existence.